Intermittent aeration improving activated granular sludge granulation for nitrogen and phosphorus removal from domestic wastewater. (September 2021) - Huang, Jiansheng; Xu, Linji; Guo, Yinying; Liu, Deshao; Chen, Shuangkou; Tang, Qian; Zheng, Haotian; Tan, Junfeng; Peng, Feng
Abstract: Given the large quantity discharge of nutrients in sewage, nitrogen and phosphorus is getting a worldwide concern. This manuscript assigned two different aeration modes of intermittent aeration/anoxia aeration and continuous aeration to study dissolved oxygen (DO) affecting contaminant removal, AGS granulation and microbial community diversity. The results demonstrated that intermittent aeration contributed to higher removal efficiencies of organics, nitrogen and phosphorus and faster granulation process, larger particle size, and more microbial communities than continuous aeration. The temporal lack of DO for intermittent aeration module did not only save approximately 40% energy but also change microbial communities. The intermittent aeration had no growth of filamentous bacteria and more microbial communities consist of Paracoccus, Delftia, Flavobacterium, Brevundimonas, Roseobacter _ clade _ CHAB - I - 5 _ lineage, which accelerated AGS granulation, and Nitrosopumilus, Nitrospina, Facultative anaerobes, Pelagibacter and UKL 13 - 1 bacteria, which played crucial roles in N and P removal. Graphical abstract: Unlabelled Image Highlights: Intermittent and continuous aeration modes were originally designed. Intermittent aeration had better performances than continuous aeration. Intermittent aeration removed maximum 98% N and 80% P. Intermittent aeration achieved AGS with larger size and faster granulation. Intermittent aeration saved 40% energy consumption.